The use of pancreatic enzyme replacement therapy in patients with a diagnosis of chronic pancreatitis and pancreatic cancer in the US is infrequent and inconsistent. Issue 10 (6th April 2020) - Forsmark, Chris E.; Tang, Gong; Xu, Hongzhi; Tuft, Marie; Hughes, Steven J.; Yadav, Dhiraj
Summary: Background: Patients with chronic pancreatitis or pancreatic cancer commonly develop exocrine pancreatic insufficiency, and may not be adequately treated with pancreatic enzyme replacement therapy (PERT). Aims: To estimate the frequency of diagnostic testing for exocrine insufficiency, and appropriate use of PERT, in a commercially insured population in the US. Methods: We utilised a nationally representative administrative database representing 48.67 million individuals in over 80 US healthcare plans to assess testing for and treatment of exocrine insufficiency in patients who received a diagnosis of chronic pancreatitis (n = 37 061) or pancreatic cancer (n = 32 461) from 2001 to 2013. We identified the details of any testing for exocrine insufficiency and PERT use. We defined appropriate PERT use as a dosage of ≥120 000 USP units of lipase daily. Multiple logistic regression was used to identify predictors of appropriate use of PERT. Results: In patients with chronic pancreatitis, 6.5% had any testing for exocrine insufficiency, 30.4% filled a prescription for PERT, and 8.5% were prescribed an adequate dose. In those with pancreatic cancer, 1.9% had testing for exocrine insufficiency, 21.9% filled a prescription for PERT, and 5.5% were prescribed an adequate dose. Number of comorbidities, testing for exocrine insufficiency, pancreatic surgery and duration of enrolment were independent predictors for use and appropriate dosing. Conclusions: Testing for exocrine insufficiency, and appropriate dosing of PERT in patients with chronic pancreatitis or pancreatic cancer, is infrequent and inconsistent in an insured US population. Efforts are needed to educate medical providers on the best practices for managing exocrine pancreatic insufficiency in these patients.